Carnosine protects human microglia against Aβ oligomers through a multimodal mechanism of action: inhibition of oxidative stress, rescue of cellular energy status, and enhancement of phagocytosis - Privitera, Anna; Cardaci, Vincenzo; Zupan, Matthew C.; Di Pietro, Lucia; Carota, Giuseppe; Sibbitts, Jay; Mangione, Renata; Graziani, Andrea; Buccarello, Lucia; Bellia, Francesco; Di Pietro, Valentina; Lazzarino, Giuseppe; et al. (Frontiers in Immunology, 2026)
IntroductionCarnosine is an endogenous dipeptide composed by β-alanine and L-histidine widely distributed in excitable tissues like muscles and brain. Carnosine participates in the cellular defenses against oxidative/nitrosative stress through a multimodal mechanism of action, including scavenging of the reactive oxygen and nitrogen species (ROS and RNS) and, in brain cells, the inhibition of amyloid-beta (Aβ) aggregation. Microglia play a central role in the pathophysiology of Alzheimer’s disease (AD), maintaining the homeostasis of the brain microenvironment. However, its hyperactivation causes an increased secretion of inflammatory mediators and free radicals, leading to neuroinflammatory phenomena that exacerbate neurodegeneration. In the present work, carnosine was tested for its ability to protect human microglial cells (HMC3) against Aβ oligomers-induced oxidative stress and energy metabolism unbalance.MethodsThe effects of carnosine to modulate nitric oxide (NO) and ROS intracellular levels were evaluated by microchip electrophoresis coupled to laser-induced fluorescence (ME-LIF), while additional stress-related parameters and cellular energy metabolism were investigated through high-performance liquid chromatography (HPLC).ResultsPre-treatment with carnosine counteracted the oxidative/nitrosative stress induced by Aβ1-42 oligomers by decreasing the intracellular levels of NO and ROS, and rescuing GSH levels. Carnosine preserved cellular mitochondrial-related energy metabolism, restoring concentrations of high-energy phosphates, nicotinic coenzymes and oxypurines, and normalizing UDP-derivatives homeostasis. Furthermore, carnosine strongly enhanced the phagocytic activity of HMC3 cells.Discussion/ConclusionThese results demonstrate the protective effects of carnosine on human microglial cells against detrimental alterations induced by Aβ oligomers, underlining the multimodal mechanism of action of this dipeptide and supporting its promising potential in the context of AD pathology.